Enhanced TLR2 responses in multiple sclerosis. (24th July 2018) - Fujiwara, M; Anstadt, E J; Flynn, B; Morse, K; Ng, C; Paczkowski, P; Zhou, J; Mackay, S; Wasko, N; Nichols, F; Clark, R B
Summary: The roles of the microbiome and innate immunity in the pathogenesis of multiple sclerosis (MS) remain unclear. We have previously documented abnormally low levels of a microbiome-derived Toll-like receptor (TLR)2-stimulating bacterial lipid in the blood of MS patients and postulated that this is indicative of a deficiency in the innate immune regulating function of the microbiome in MS. We postulated further that the resulting enhanced TLR2 responsiveness plays a critical role in the pathogenesis of MS. As proof-of-concept, we reported that decreasing systemic TLR2 responsiveness by administering very low-dose TLR2 ligands attenuated significantly the mouse model of MS, experimental autoimmune encephalomyelitis. Studies of Toll-like receptor responses in patients with MS have been conflicting. Importantly, most of these investigations have focused on the response to TLR4 ligation and few have characterized TLR2 responses in MS. In the present study, our goal was to characterize TLR2 responses of MS patients using multiple approaches. Studying a total of 26 MS patients and 32 healthy controls, we now document for the first time that a large fraction of MS patients (50%) demonstrate enhanced responsiveness to TLR2 stimulation. Interestingly, the enhanced TLR2 responders include a significant fraction of those with progressive forms of MS, a subset of patients considered unresponsive to adaptive immune system-targeting therapies. Our results suggest the presence of a pathologically relevant TLR2 related innate immune abnormality in patients with both relapsing–remitting and progressive MS. These findings may have significant implications for understanding the role of innate immunity in the pathogenesis of MS. Graphical Abstract: